Nisin A-producing Lactococcus cremoris formulations for pre- and post-milking teat disinfection modulate the bovine milk microbiota - Alessandra Gazzola; Camilla Ceccarani; Bianca Castiglioni; Filippo Biscarini; Stefano Morandi; Tiziana Silvetti; Renata Piccinini; Milena Brasca; Paola Cremonesi (BMC Veterinary Research)
Abstract Background Bovine mastitis is a major challenge in dairy farms. Since the agents commonly used for pre- and post-dipping can affect the udder health by modifying milk microbiota, alternative products are needed. This study aimed to evaluate the effect of the use of pre- and post-dipping formulations containing the fermented broth of Nisin A-producing Lactococcus cremoris FT27 strain (treated group, TR) on the abundance and biodiversity of milk microbiota as compared to iodine-based commercial disinfectants (control group, CTR) during a three-month trial. The experiment was conducted on 20 dairy cows, divided into two groups (CTR and TR) of 10 lactating cows each. Milk samples were collected from two selected healthy quarters of each cow at 3 time-points. Microbial communities were investigated by cultural and sequence-based methods, and analyzed through bioinformatic and statistical approaches. Results Clear differences in bacterial community composition were observed among groups, with higher species richness in TR, especially of Staphylococcus, Enterococcus, Lactococcus, and Streptococcus genera. The microbiota was dominated by Firmicutes, followed by Actinobacteriota, Proteobacteria, and Bacteroidota. Staphylococcaceae family was significantly higher in TR (p < 0.009), whereas Carnobacteriaceae, Mycobacteriaceae, and Pseudomonadaceae were significantly lower (p = 0.005, p = 0.001, and p = 0.040, respectively). CTR had considerably higher abundances of the genera Alkalibacterium (p = 0.011), Pseudomonas_E (p = 0.045), Corynebacterium (p = 0.004), and Alloiococcus (p = 0.004), and lower abundances of Staphylococcus (p < 0.009). Milk microbiota changed noticeably during the experimental period, regardless of treatment. A significant decrease was observed in both groups for Firmicutes_A phylum, with an increment in Actinobacteriota phylum, Propionibacteriaceae family, and Cutibacterium genus. Streptococcaceae significantly decreased in CTR (p = 0.013) and rose in TR (p = 0.001). Several differences were observed between the two groups during the experimental period. Streptococcus genus almost disappeared in CTR (p = 0.013), whereas it significantly increased in TR (p = 0.001). Three and twelve enriched groups were significantly identified respectively in CTR and TR using LEfSe. Conclusions The use of Nisin A-based teat dip formulations could be linked to greater microbial diversity compared to commercial products. Despite the influence of seasonality, the experimental formulations maintained higher milk biodiversity, suggesting that lactic acid bacteria metabolites prevent alterations in the milk microbiota.